TANGGUNG JAWAB MASKAPAI PENERBANGAN TERHADAP HILANGNYA BAGASI PENUMPANG BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN - Eka Susanti (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT The research aimed at investigating and comprehending the flight corporation responsibility implementation on the passengers who underwent the losses, and the efforts which could be taken by the passengers towards the flight corporations on the losses they suffered.All the data obtained in the research either the primary or secondary data were analysed using the qualitative analysis technique, the data were then described by analyzing the existing problems.The research result indicates that the flight corporations having the role as the air carriers have the responsibilities on the passengers. The responsibilities are in the forms of the responsibilities on the accidents, goods losses, and departure times. The responsibilities are regulated by the clear rules in the Acts of Republic of Indonesia Number 1 Year 2009 concerning the flight, and the Regulation of the Minister of Transportation Number 77 Year 2011 concerning the responsibilities of the air carries. The research indicates that the implementation of the flight corporation responsibilities to the passengers has not been optimal. It can be seen that the flight corporations are still frequently escaped from their responsibilities in giving the compensations to the passengers. As for the next control efforts of the Airline is to disseminate the news throught a variety of visual and print media advertising in the form of social services or appeal installe in the airport area of about breaches carry valuables in the trunk. The warning sanction or hold a certificate issued to the airline if it is not liable for damages suffered by passengers.  Keywords: Responsibility Airlines, Airlines, baggage Goods Carrying, passangers, Compensation.